Sturm-Liouville problems with retarded argument and a finite number of transmission conditions - Erdogan Sen (Electronic Journal of Differential Equations, 2017)
The main goal of the present paper is to study the asymptotic behaviour of eigenvalues and eigenfunctions of a discontinuous boundary-value problem with retarded argument with a finite number of transmission conditions.